MOF-derived noble-metal-free Cu/CeO2 with high porosity for the efficient water–gas shift reaction at low temperatures. Issue 16 (30th July 2019) - Jampaiah, Deshetti; Damma, Devaiah; Chalkidis, Anastasios; Singh, Mandeep; Sabri, Ylias M.; Mayes, Edwin L. H.; Bansal, Vipul; Bhargava, Suresh K.
Abstract : A metal organic framework templated Cu/CeO2 catalyst exhibited enhanced catalytic performance for the water–gas shift reaction at low temperatures. Abstract : Herein, we report a highly efficient nanoporous Cu/CeO2 catalyst from metal organic frameworks (MOFs) for low-temperature WGS reaction. The MOF template approach delivered Cu/CeO2 nanocatalysts with larger surface areas and higher Cu dispersion, resulting better redox behaviour compared to Cu/CeO2 which was synthesized by a conventional co-precipitation method. The MOF derived Cu/CeO2 catalyst showed excellent catalytic performance (>90% CO conversion) for the WGS reaction at low temperature. It also maintained a long-term stability of 90 h operation, after which the CO conversion was still greater than 80%. Our results present advances in the exploitation of MOF templated nanoporous catalysts not only for WGS reaction but also for other catalytic applications.